A new method for the covalent attachment of DNA to a surface for single-molecule studies - Schlingman, Daniel J. (2010)
Attachments between DNA and a surface or bead are often necessary for single-molecule studies of DNA and DNA-protein interactions. In single-molecule mechanical studies using optical or magnetic tweezers, such attachments must be able to withstand the applied forces. Here we present a new method for covalently attaching DNA to a glass surface, which uses N-hydroxysuccinimide (NHS) modified PEG that is suitable for high-force single-molecule mechanical studies. A glass surface is coated with silane-PEG-NHS and DNA is covalently linked through a reaction between the NHS group and an amine modified nucleotide that has been incorporated into the DNA. After DNA attachment, non-reacted NHS groups are hydrolyzed leaving a PEG-covered surface which has the added benefit of reducing non-specific surface interactions. This method permits specific binding of the DNA to the surface through a covalent bond. At the DNA end not attached to the surface, we attach a streptavidin-coated polystyrene bead and measure force-versus-extension using an optical trap. We show that our method allows a tethered DNA molecule to be pulled through its overstretching transition (>60 pN) multiple times. We anticipate this simple yet powerful method will be useful for many researchers.